"Classifying" Margarine: The Early Class-Based Marketing of a Butter Substitute in Sweden (1923-1933). Issue 1 (2nd January 2023) - O'Hagan, Lauren Alex
Abstract: From its inception in 1869, margarine was considered a working-class food, associated with poverty and inferiority. In the early twentieth century, Swedish margarine brands set about to change public perception of the product, investing vast sums of money in extensive marketing campaigns to showcase it as suitable for the middle classes. However, wanting to retain as much market share as possible, they also continued to direct margarine advertisements at the working classes. Thus, a seemingly paradoxical situation emerged where the same brands, often in the same newspapers, published advertisements aimed at two distinct audiences. This paper uses multimodal critical discourse analysis to examine a large body of margarine advertisements produced in Sweden between 1923 and 1933. Specifically, it considers how brands appealed to either working-class or middle-class identities, socialisation, relationships, and rituals in the arguments they put forward about the values of margarine. It finds that middle-classadvertisements were focused on promoting margarine as exclusive and luxurious, challenging prejudices and encouraging them to learn from the working classes, while working-class advertisements centred around respectability and keeping up appearances, valuing frugality and thrift and commending traditional ways of life and regional/national customs.